Prosthetic valve endocarditis: who needs surgery? A multicentre study of 104 cases. Issue 7 (14th June 2005) - Habib, G; Tribouilloy, C; Thuny, F; Giorgi, R; Brahim, A; Amazouz, M; Remadi, J-P; Nadji, G; Casalta, J-P; Coviaux, F; Avierinos, J-F; Lescure, X; et al.
Abstract : Objectives: To identify the prognostic markers of a bad outcome in a large population of 104 patients with prosthetic valve endocarditis (PVE), and to study the influence of medical versus surgical strategy on outcome in PVE and thus to identify patients for whom surgery may be beneficial. Design: Multicentre study. Methods and results: Among 104 patients, 22 (21%) died in hospital. Factors associated with in-hospital death were severe co-morbidity (6% of survivors v 41% of those who died, p = 0.05), renal failure (28% v 45%, p = 0.05), moderate to severe regurgitation (22% v 54%, p = 0.006), staphylococcal infection (16% v 54%, p = 0.001), severe heart failure (22% v 64%, p = 0.001), and occurrence of any complication (60% v 90%, p = 0.05). By multivariate analysis, severe heart failure (odds ratio 5.5) and Staphylococcus aureus infection (odds ratio 6.1) were the only independent predictors of in-hospital death. Among 82 in-hospital survivors, 21 (26%) died during a 32 month follow up. A Cox proportional hazards model identified early PVE, co-morbidity, severe heart failure, staphylococcus infection, and new prosthetic dehiscence as independent predictors of long term mortality. Mortality was not significantly different between surgical and non-surgical patients (17% v 25%, respectively, not significant). However, both in-hospital and long term mortality were reduced by a surgical approach in high risk subgroups of patients with staphylococcal PVE and complicated PVE. Conclusions: Firstly, PVE not only carries a high in-hospital mortality risk but also is associated with high long term mortality and needs close follow up after the initial episode. Secondly, congestive heart failure, early PVE, staphylococcal infection, and complicated PVE are associated with a bad outcome. Thirdly, subgroups of patients could be identified for whom surgery is associated with a better outcome: patients with staphylococcal and complicated PVE. Early surgery is strongly recommended for these patients.